152k views
1 vote
What is the solution to the equation 6y-2 (y + 1) = 3(y-2) + 6

2 Answers

6 votes

Answer:

y=2

Explanation:

6y-2 (y + 1) = 3(y-2) + 6

6y-2y-2 = 3y-6+6 *simplify*

4y-2 = 3y *minus 4y on both sides*

-2 = -y *swich the sign for both*

2=y or y=2

User Shnd
by
4.8k points
1 vote

Answer:

2

Explanation:


6y-2y-2=3y-6+6\\4y-2=3y\\4y-3y=2\\y=2

User Spacenick
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.